The contribution of urban gravity survey to the subsurface geological structure of the Athens basin (Greece) - Dilalos, S.; Alexopoulos, J.D.; Lozios, S. (Near Surface Geoscience 2019 - 25th European Meeting of Environmental and Engineering Geophysics, 2019)
The gravity method has been applied, with a total of 1.122 gravity measurements for the subsurface investigation of the geotectonic structure beneath the urban and sub-urban areas of Athens basin. The aim was to gather new information for the subsurface geological and tectonic structure of Athens basin and re-assess the seismic hazard risk of the area that may damage its infrastructures. The standard corrections have been applied (drift, tide, latitude, free-air, Bouguer, terrain ones) along with an additional Building Correction that has been calculated based on the urban characteristics. Afterwards, the isolation of the residual anomaly has been accomplished with the contribution of the Fourier filters and the analysis of the power energy spectrum. The processing results provided important data regarding the geological and tectonic structure beneath the Quaternary formations that cover the basin. We managed to verify already proposed concealed fault zones or even discover and propose new ones that may affect the city in the future by generating disastrous earthquakes. In the context of the interpretation, two geophysicalgeological profiles have been constructed, along which the geotectonic regime of the subsurface is clarified.